CFD Study of the Bulbous Bow Effect on the Resistance of the Tanker-KVLCC2 - عباس نوار; عديرة بشار (Latakia University Journal -Engineering Sciences Series, 2021)
In this paper, the flow around the Tanker KVLCC2 body has been analyzed and studied using the Computational Fluid Dynamic (CFD) technology. The study focuses on the changes in the Tanker resistance performance by adding the bulbous bow. The RANS method, Volume of Fluid (VOF), and turbulence model were used to solve Navier Stocks Equations. The resistance of the tanker with bulbous bow was calculated, as well as the fields of velocity, and turbulent kinetic energy. The obtained results were compared with the experimental results. The comparison demonstrated a good agreement between the CFD and EFD results, which confirms the quality of CFD technology. The total resistance of three different tanker models of KVLCC2 (with and without bulbous bow) was calculated and compared with each other, to show the effect of bulbous bow on the resistance of the ship.